The Sustainable Use of Waste Glass Powder in Concrete-Filled Steel Tubes: A Mechanical and Economic Analysis - Yi Zhao; Bin Meng; Xiaosan Yin; Yijie Bao (Buildings)
By incorporating waste glass into concrete-filled steel tube columns, this study aims to mitigate the environmental impacts associated with the production of cement and concrete while simultaneously reducing costs. This research investigates the effects of replacing the cement in concrete with an equal mass of waste glass powder (WGP) at five different replacement rates—0%, 5%, 15%, 30%, and 60%—and focuses on the mechanical behaviors and value coefficients of concrete-filled steel tubes (CFSTs), which are evaluated through axial compression tests and value engineering methods. The results indicate that the loading process for waste glass powder CFST (WGPCFST) short columns closely resembles that of ordinary CFST short columns. While the bearing capacity of WGPCFST short columns decreased with an increasing WGP content, no significant reduction was observed compared to ordinary CFST short columns. Notably, at replacement rates of 5% to 15%, WGPCFST short columns exhibited an enhanced deformational capacity—at least 14% greater—compared to their ordinary counterparts, suggesting that WGPCFSTs are a promising alternative to CFSTs. Additionally, value engineering results revealed that the highest integrated value was achieved at a WGP replacement rate of 5%. Furthermore, a significant negative correlation was found between the value coefficient and the WGP replacement rate.